Multiple Beam Selection for Combing M2M Communication Networks and Cellular Networks with Limited Feedback - Xiaoning Zhang; Lin Bai; Wenyang Guan (International Journal of Distributed Sensor Networks)
We study the scenario in which a large number of machine-type communication devices (MTCDs) communicate with each other by utilizing the help of the base station (BS) through some MTCD gateways. We consider an overlay mode of an orthogonal frequency division multiple access (OFDMA) based cellular system using orthogonal beamforming to provide broadband wireless access for the MTCD gateways. In order to avoid the interference with mobile users, the beamforming vectors to the MTCD gateways have to be orthogonal to the channel vectors of mobile users, which become a beamforming constraint for the MTCD gateways. However, with limited feedback of channel state information (CSI) at a BS, the orthogonal beamforming constraints may not be achieved. In such a practical case, conventional feedback schemes are feasible but not efficient due to the orthogonality constraints. In this paper, we propose a novel multiple beam selection (MBS) approach with limited feedback for MTCD gateways by taking into account the previous orthogonality constraints. Simulation results show that the performance improvement of the proposed approach over the conventional ones is generally about 10% when a BS is equipped with an array of 6 elements.